Analisis Hukum Perkawinan Islam terhadap Pasal 16 The Universal Declaration of Human Right - Deden Abdul Malik; Tajul Arifin; Ine Fauzia (CV Rewang Rencang, 2025)
Interfaith marriage in Islam and Article 16 of the Universal Declaration of Human Rights (UDHR) show significant differences in legal and ethical approaches. In Islamic law, interfaith marriage is strictly regulated, with permission for Muslim men to marry Ahl al-Kitab women (Jews and Christians), but prohibiting Muslim women from marrying non-Muslim men. This aims to maintain the sustainability of Islamic beliefs in the family. Meanwhile, the UDHR emphasizes the right of individuals to choose a life partner without discrimination of religion, race, or nationality. This study aims to find out how the law of interfaith marriage, according to Islamic Marriage law allows marriage between a Muslim man and a woman Ahl al-Kitab, there are certain conditions that must be met, including maintaining Islamic norms and respecting the rights of the couple Various opinions of scholars regarding interfaith marriage, especially related to the different views of madhhab, reflect the complexity and variation in the understanding of Islamic law on this topic. Article 16 of the UDHR, which affirms the freedom of individuals in marriage without discrimination, is contrary to the principles of Islamic law that further restrict interfaith marriage, describing the tension between human rights and religious teachings in the context of interfaith marriage.